PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. JESSINDO PRAKARSA - Aldi; Irma (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
Human resources (HR) play a very dominant role in company activities so that the success or failure of the company in achieving goals depends very much on the ability of HR or employees because a superior company is a company that has good employee performance so that company goals can be achieved. The purpose of this study is to determine and analyze the Effect of Work Environment, Work Motivation and Work Discipline on Employee Performance at PT. Jessindo Prakarsa. The type of research used is quantitative research with research methods in the form of data collection using questionnaires. The data analysis model used is multiple linear regression analysis. Sample selection is done by purposive sampling. The sample amounted to 30 respondents, using multiple linear regression analysis. The results of the regression test showed that 18.7% of employee performance factors could be explained by work environment, work motivation and work discipline while the remaining 81.3% were influenced by other variables that were not included in this study. The results of the F test show that simultaneously the variables of work environment, work motivation and work discipline simultaneously have a positive and significant effect on employee performance. While the results of the t test show that the variables of work motivation and work discipline are persial, these two variables do not have a positive and significant effect on employee performance.